A case of synchronous papillary and clear cell carcinoma in the same kidney - Tele, Jyoti Shankar; Shah, Anita; Kushwaha, Harshul (International Journal of Research in Medical Sciences, 2017)
Renal Cell Carcinoma (RCC) comprises 2-3% of all cancers. Bilateral coexistent benign and malignant renal tumors have been defined in many reports. However, unilateral synchronous malignant tumors of different histologic subtypes are very rare and only a few such cases have been reported. Herein we describe a 56 year old male patient with coexistent clear cell RCC and papillary RCC in his left kidney that were successfully treated with radical nephrectomy.